Seed bio-priming with beneficial Trichoderma harzianum alleviates cold stress in maize - Mehdi Afrouz; R Z. Sayyed; Bahman Fazeli-Nasab; Ramin Piri; WaleedHassan Almalki; Betty Natalie Fitriatin (PeerJ, 2023)
Maize is one of the major crops in the world and the most productive member of the Gramineae family. Since cold stress affects the germination, growth, and productivity of corn seeds, the present study aimed to investigate the effect of seed biopriming with Trichoderma harzianum on the tolerance of two genotypes of maize seedlings to cold stress. This study was conducted in triplicates in factorial experiment with a complete randomized block design (CRBD). The study was conducted in the greenhouse and laboratory of the University of Mohaghegh Ardabili, Ardabil, Iran. Experimental factors include two cultivars (AR68 cold-resistant and KSC703 cold-sensitive maize cultivars), four pretreatment levels (control, biopriming with T. harzianum, exogenous T. harzianum, and hydropriming), and two levels of cold stress (control and cold at 5 °C) in a hydroponic culture medium. The present study showed that maize leaves’ establishment rate and maximum fluorescence (Fm) are affected by triple effects (C*, P*, S). The highest establishment (99.66%) and Fm (994 units) rates were observed in the KP3 control treatment. Moreover, among the pretreatments, the highest (0.476 days) and the lowest (0.182 days) establishment rates were related to P0 and P3 treatments, respectively. Cultivar A showed higher chlorophyll a and b, carotenoid content, and establishment rate compared to cultivar K in both optimal and cold conditions. The highest root dry weight (11.84 units) was obtained in cultivar A with P3 pretreatment. The pretreatments with T. harzianum increased physiological parameters and seedling emergence of maize under cold and optimal stress conditions. Pretreatment and cultivar improved catalase activity in roots and leaves. Higher leaf and root catalase activity was observed in the roots and leaves of cultivar K compared to cultivar A. The cold treatment significantly differed in peroxidase activity from the control treatment. Cultivar K showed higher catalase activity than cultivar A. The main effects of pretreatment and cold on polyphenol oxidase activity and proline content showed the highest polyphenol oxidase activity and proline content in hydropriming (H) treatment. Cold treatment also showed higher polyphenol oxidase activity and proline content than cold-free conditions.